PENGARUH MEDIA SOSIAL INSTAGRAM @lyfewithless SEBAGAI KOMUNITAS GAYA HIDUP MINIMALIS TERHADAP SIKAP BIJAK BERKONSUMSI FOLLOWERS - Tasya Indah Firdausi; Vera Wijayanti Sutjipto; Marisa Puspita Sary; Elisabeth Nugrahaeni Prananingrum; K. Y.S. Putri; Nada Arina Romli (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
The close use of social media in today's society allows all information to be easily disseminated, including disseminating positive information or education to a wide audience, as done by the Lyfe With Less community as a minimalist lifestyle community that utilizes Instagram social media as one of their campaign media. The purpose of this study is to determine the effect of Instagram social media @lyfewithless as a minimalist lifestyle community on the wise consumption attitude of followers. There are two variables in this study, namely social media variables with dimensions of context, communications, collaboration, and connections, and attitude variables with dimensions of cognitive components, affective components, and conative components. The theory used in this research is social judgment theory which explains how individuals have an assessment of the information or messages they get. This study used a survey method with data analysis techniques in the form of descriptive univariate, namely measuring the mean per variable, and bivariate, namely with simple linear regression analysis to determine the effect of the two variables tested. The results showed that there was a strong influence between Instagram social media @lyfewithless as a minimalist lifestyle community on followers' wise consumption attitudes.